Hubungan Kompetensi Sosial Guru Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Kristen Kelas IX SMP Satu Atap Negeri 5 Pangururan - Riama Marito Simorangkir; Binur Panjaitan; Risden Anakampun; Oktober Tua Aritonang; Goklas J Manalu (Publisher STPKat, 2023)
The aim of this research is to determine the relationship between teacher social competence and the learning motivation of class VIII Christian Religious Education students at SMP Satu Roof Negeri 5 Pangururan. The method used in this research is a descriptive quantitative research method. The population is all 102 students of VIII SMP Satu Atap Negri 5 Pangururan for the 2022/2023 academic year and a sample of 35 people was determined using a random sampling technique. Data was collected using a positive closed questionnaire with 31 items, namely 20 items for variable data as follows: 1) test the positive relationship obtained by the value rxy = 0.574 > rtable(a=0.05,n=35) = 0.334, thus it is known that there is a positive relationship between variable X and variable Y. 2) Test the relationship The significant value obtained is tcount= 4.026 > ttable(a=0.05, dk=n-2=33)=2.042, thus there is a significant relationship between variable X and variable Y. So Ha says there is a relationship between teacher social competence and learning motivation Class VIII Christian Religious Education students at One Roof Middle School 5 Pangururan were accepted and H0 which said there was no relationship was rejected.